Dative B←N bonds based crystalline organic framework with permanent porosity for acetylene storage and separation. Issue 3 (20th December 2022) - Wang, Weize; Wang, Linxia; Du, Fei; Wang, Gang-Ding; Hou, Lei; Zhu, Zhonghua; Liu, Bo; Wang, Yao-Yu
Abstract : Utilizing a bifunctional organic linker, the first crystalline organic framework based on dative B←N bonds with permanent porosity was synthesized in one step. It sets a benchmark for C2 H2 uptake and shows effective C2 H2 /CO2 separation. Abstract : The utilization of dative B←N bonds for the creation of crystalline organic framework (BNOF) has increasingly received intensive interest; however, the shortage of permanent porosity is an obstacle that must be overcome to guarantee their application as porous materials. Here, we report the first microporous crystalline framework, BNOF-1, that is assembled through sole monomers, which can be scalably synthesized by the cheap 4-pyridine boronic acid. The 2D networks of BNOF-1 were stacked in parallel to generate a highly porous supramolecular open framework, which possessed not only the highest BET surface area of 1345 m 2 g −1 amongst all of the BNOFs but also features a record-high uptake of C2 H2 and CO2 in covalent organic framework (COF) materials to date. Dynamic breakthrough experiments demonstrated that BNOF-1 material can efficiently separate C2 H2 /CO2 mixtures. In addition, the network can be regenerated in organic solvents with no loss in performance, making its solution processable. We believe that BNOF-1 would greatly diversify the reticular chemistry and open new avenues for the application of BNOFs.